2013
DOI: 10.1371/journal.pntd.0002363
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mouse Melioidosis with Meningitis by CD11b+ Phagocytic Cells Harboring Intracellular B. pseudomallei as a Trojan Horse

Abstract: BackgroundApproximately 3–5% of patients with melioidosis manifest CNS symptoms; however, the clinical data regarding neurological melioidosis are limited.Methods and FindingsWe established a mouse model of melioidosis with meningitis characterized by neutrophil infiltration into the meninges histologically and B. pseudomallei in the cerebrospinal fluid (CSF) by bacteriological culturing methods. As the disease progresses, the bacteria successively colonize the spleen, liver, bone marrow (BM) and brain and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…This route of entry has been suggested for L. monocytogenes (279), B. pseudomallei (280), S. suis (146), and M. tuberculosis (281). In C57BL/6 ϫ DBA/2 mice, L. monocytogenes-infected peripheral blood leukocytes disseminated to the CNS and were shown to induce brain colonization more efficiently than extracellular L. monocytogenes (279).…”
Section: Trojan Horse Penetration Of Brain Microvascular Endothelial mentioning
confidence: 93%
See 3 more Smart Citations
“…This route of entry has been suggested for L. monocytogenes (279), B. pseudomallei (280), S. suis (146), and M. tuberculosis (281). In C57BL/6 ϫ DBA/2 mice, L. monocytogenes-infected peripheral blood leukocytes disseminated to the CNS and were shown to induce brain colonization more efficiently than extracellular L. monocytogenes (279).…”
Section: Trojan Horse Penetration Of Brain Microvascular Endothelial mentioning
confidence: 93%
“…These data suggest that B. pseudomallei-infected CD11b ϩ cells within the spleen and bone marrow may disseminate to the CNS and contribute to the pathogenesis of neurological melioidosis with meningitis. Further experiments demonstrated that the expression of selectin on B. pseudomallei-infected CD11b ϩ cells was required for the development of meningitis in recipient mice (280).…”
Section: Trojan Horse Penetration Of Brain Microvascular Endothelial mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, B. pseudomallei is an intracellular pathogen capable of persistence within different host cells and rapid systemic spread to multiple organs within hours of exposure (6,29,30). Recently, colonization of the brain in a murine model of neurological melioidosis was found to occur via the transmigration of B. pseudomallei-infected CD11b ϩ phagocytes across endothelial cells (31). Therefore, a mechanism whereby B. pseudomallei uses DC as a vehicle for dissemination is plausible due to the rapid progression of melioidosis from a localized infection to septicemia and involvement of multiple organs.…”
Section: Both Human and Murine DC Stimulated With Heat-killed B Pseumentioning
confidence: 99%